A Complication of the use of an Intra-Osseous Needle. Issue 2 (1st June 2009) - Fenton, P.; Bali, N; Sargeant, I; Jeffrey, SLA
Abstract : Intraosseous needles provide an important alternative to intravenous access for administration of drugs, fluids and blood products in the emergency management of trauma patients. This case report highlights one potential complication of the use of one brand of IO needle.